If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8y + 1) + -1(-7y + -2) = -1 Reorder the terms: -1(1 + 8y) + -1(-7y + -2) = -1 (1 * -1 + 8y * -1) + -1(-7y + -2) = -1 (-1 + -8y) + -1(-7y + -2) = -1 Reorder the terms: -1 + -8y + -1(-2 + -7y) = -1 -1 + -8y + (-2 * -1 + -7y * -1) = -1 -1 + -8y + (2 + 7y) = -1 Reorder the terms: -1 + 2 + -8y + 7y = -1 Combine like terms: -1 + 2 = 1 1 + -8y + 7y = -1 Combine like terms: -8y + 7y = -1y 1 + -1y = -1 Solving 1 + -1y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1y = -1 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = -1 + -1 -1y = -1 + -1 Combine like terms: -1 + -1 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2
| 87=a+48 | | f+6=87 | | -5(-9z+1)=2(8+7z) | | 54=82-y | | 25-b=15 | | c+15=76 | | c+15=76 | | x=18+2x | | 4=s/9 | | 57-t=49 | | (x+2)/3-4x=8 | | y^2-13y+36/3y-12 | | x+3-4x=0 | | 12y=6-2x | | 3(x)=1/2x+5 | | 9+v=36 | | 7k-21=3k-5 | | 17=p-5 | | 31=3+m | | k+36=40 | | 9x^4+12x^2+4= | | 65-h=54 | | x-51=27 | | 54=6z | | 14=7r | | 8x+33=5x+87 | | 60y^2-51y-72=0 | | 3x^2-9x=30 | | d-(-4)=25 | | (2x+7)(x-8)=0 | | 3x^2+17x-12=0 | | 9g-6=3(4g+5) |